Distributional and Welfare Effects of Including Corn into NAFTA and the Social, Economic, Political and International Repercussions for Mexico - Mendoza, Sylvia (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: This thesis explores the possible causal relationship between an increase in inequality and poverty in Mexico and the inclusion of corn into the North American Free Trade Agreement (NAFTA). Since trade in this crop is mainly between Mexico and the United States, trade with Canada will not be taken into consideration. This analysis uses several economic parameters that determine which groups of the population are affected by maize price drops and supply and demand shifts, such as budget allocations, an Engel curve, the determination of buyers and sellers, and cross-price elasticities of white and yellow corn. The elimination of the Mexican State Trading Enterprise, CONASUPO, is used as a base case in order to determine if NAFTA was indeed what caused these adverse distributional effects. To determi! ne these effects and the different economic parameters used, econometric studies and models by Antonio Yunez-Naude, Alain de Janvry, and Santiago Levy, among others, are described and analyzed. This thesis concludes that NAFTA has caused some but not all of the documented adverse distributional effects. The analysis outlines policy recommendations and briefly describes possibilities for renegotiation.